Revolutionary Aspects of Artificial Intelligence in Drug Discovery and Development - Neetu Dharu N; Iram Fatema Siddique; Dr. Gautam B. Sonara; Dr. Manish B. Goyani (Asian Journal of Pharmaceutical Research and Development, 2026)
The pharmaceutical sector is shifting with the help of artificial intelligence (AI), which has enhanced the accuracy of drug development and discovery. AI enables predictive modeling of bioactivity and toxicity, accelerates virtual screening and lead optimization, enhances the processing of complex biological data sets, and streamlines clinical trial design and patient recruitment. To analyze how AI has transformed the pharmaceutical sector, enhanced product life cycle management, and facilitated data-informed decision-making from target candidate selection to market, this research includes high-impact studies. We also address operational, ethical, and regulatory challenges as well as what needs to be done to ensure that AI delivers its promise of creating better, faster, and cheaper cures.